Peran Shopping Enjoyment, Price Discount dan Live Streaming terhadap Impulsive Buying - Themba, Orfyanny Syahreffy; Akob, Rezky Arianty; Mokhtar, Susiana (Al-Buhuts, 2024)
The purpose of this study is to test the effect of shopping enjoyment, price discount and partial live streaming on impulse buying. The methodology used in this article is a type of quantitative research, a descriptive method with an explanatory survey approach. The population in this study is the people of Makassar City who have shopped at Shopee e-commerce whose number is not known for sure, while the sampling method uses non-probability sampling with purposive sampling techniques. The number of samples used in this study was 100 respondents. This study uses the Accidental Sampling technique. The data analysis techniques used in this study are descriptive analysis, classical assumption test and multiple linear regrelis analysis. The results of this study found that shopping enjoyment has a partial effect on impulse buying, price discounts have a partial effect on impulse buying and live streaming has a partial effect on impulse buying.